Nematode infection mimicking paratesticular malignancy. (10th December 2013) - Kallampallil, Jins; Wood, Sarah J; O'Dempsey, Timothy; Craigie, Ross J
Abstract : Paratesticular swellings pose a diagnostic dilemma due to concerns over malignancy. We present a case of paratesticular swelling in a 13-year-old boy as a result of Dirofilaria immitis infection. The boy presented with a 2-month history of right testicular discomfort associated with an irregular mass within the scrotum.